Promoting New Approach Methodologies (NAMs) for research on skin color changes in response to environmental stress factors: tobacco and air pollution - Bouchard, Katherine Virginia; Costin, Gertrude-Emilia (Frontiers in Toxicology, 2023)
Aging is one of the most dynamic biological processes in the human body and is known to carry significant impacts on individuals’ self-esteem. Skin pigmentation is a highly heritable trait made possible by complex, strictly controlled cellular and molecular mechanisms. Genetic, environmental and endocrine factors contribute to the modulation of melanin’s amount, type and distribution in the skin layers. One of the hallmarks of extrinsic skin aging induced by environmental stress factors is the alteration of the constitutive pigmentation pattern clinically defined as senile lentigines and/or melasma or other pigmentary dyschromias. The complexity of pollutants and tobacco smoke as environmental stress factors warrants a thorough understanding of the mechanisms by which they impact skin pigmentation through repeated and long-term exposure. Pre-clinical and clinical studies demonstrated that pollutants are known to induce reactive oxygen species (ROS) or inflammatory events that lead directly or indirectly to skin hyperpigmentation. Another mechanistic direction is provided by Aryl hydrocarbon Receptors (AhR) which were shown to mediate processes leading to skin hyperpigmentation in response to pollutants by regulation of melanogenic enzymes and transcription factors involved in melanin biosynthesis pathway. In this context, we will discuss a diverse range of New Approach Methodologies (NAMs) capable to provide mechanistic insights of the cellular and molecular pathways involved in the action of environmental stress factors on skin pigmentation and to support the design of raw ingredients and formulations intended to counter their impact and of any subsequently needed clinical studies.